Social Media use as a Determinant of Knowledge Sharing Practices by Librarians in Tertiary Institutions in Lagos State, Nigeria - Obioma, Frances Uchechi (West African Journal of Open and Flexible Learning, 2016)
The proliferation of information and communication technology has had a significant influence on knowledge sharing practices in organizations. This has raised the consciousness of libraries to adopt the use of social media for the exchange of knowledge. Studies have indicated that knowledge sharing practices are not fully integrated in most libraries. Hence, this study investigated the extent to which social media is used to share knowledge in tertiary institutions in Lagos State, Nigeria. The survey research design was used for the study. The population of the study consisted of all 204 librarians in 21 tertiary institutions in Lagos State. Total enumeration was used for the study. Data collected were analysed using descriptive statistics for the research questions while linear regression was used to test the hypothesis. Findings revealed that social media use (B =.377, p
Keywords: Social media Use; Knowledge Sharing practice; Librarian; Tertiary Institution